Intraseasonal oscillations and the Southeast Asian monsoon onset - Loechl, Erica M., author (Colorado State University. Libraries, 2001)
The role of intraseasonal oscillations as a triggering mechanism for the Southeast Asian monsoon (SEAM) is investigated through a detailed study of the 1998 SEAM and expanded analysis to include the 20 years from 1979-1998. Spectral analysis of outgoing longwave radiation (OLR) at each gridpoint over the South China Sea (SCS) (10-20° N, 110-120° E) revealed the presence of intraseasonal oscillations with periods of 12-24 days and 30-60 days during the monsoon season. The SCS is an area of maximum variability for both of these oscillations during the SEAM onset. The monsoon onset was defined as the first day of sustained convection (based on analysis of OLR) and the commencement of southerly and westerly winds over the SCS. The range of SEAM onset dates for the 20 year period was from 10 May - 15 June. The onset timing was considered normal if it occurred between 11 May - 31 May. Analysis of band-pass filtered OLR, 850 and 200 mb winds suggest the 1998 SEAM onset was triggered by the nearly simultaneous arrival of the 12-24 day and 30-60 day oscillations into the SCS. The main component of the 12-24 day oscillation developed in the northwest Pacific near Japan and propagated southwestward into the SCS. The 30-60 day oscillation is comprised of the eastward-moving Madden-Julian oscillation {MJO) and the northward-moving monsoon trough. Lag regression analysis revealed circulation and convection patterns of the intraseasonal oscillations for the 20 years to be similar to the patterns seen in 1998. However, the oscillations appeared to be stronger during the monsoon onsets compared to the entire monsoon seasons. Significant midlatitude influence on the SCS during the onset was observed in the regressions in the form of an upper and lower level wave train that extended from the SCS into the northern Pacific. The northern part of the SCS (15-20° N) served as a "transition-zone" between midlatitudes and the tropics. Regressions based on this area displayed characteristics of both midlatitude and tropical influence during the SEAM onset. The interannual variability of the onset timing and intraseasonal oscillations was assessed by catagorizing each year according to the onset timing, presence of intraseasonal oscillations at the onset, and ENSO phase. Years where both the 12-24 day and 30-60 day oscillation were present at the onset tended to have normal onsets. Years where only the 30-60 day mode was present at the SEAM onset had the earliest onsets and years where neither oscillation was present at the SEAM onset had the latest onsets. It appears that the existence of intraseasonal oscillations assists the monsoon onset and can cause it to happen earlier than it would otherwise occur. However, monsoon onsets will occur despite the absence of such oscillations - they simply will occur later. A direct link between the onset timing and ENSO events was not obvious from this study.
Spring 2001.
Also issued as Erica M. Leochl's thesis (M.S.) -- Colorado State University, 2001.
Keywords: Monsoons -- Southeast Asia